2019
DOI: 10.3390/su11184877
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Mitigation Strategies of Port Selection and Multimodal Transport Operations—A Case Study of Northeast China

Abstract: In the last few decades, the progression of climate change has made people aware of the need to reduce CO2 emissions. In this study, the effect of this awareness on container transport in Northeast China is used as an empirical case study. Firstly, we propose that the freight demand index, calculated by the entropy weight TOPSIS (technique for order preference by similarity to an ideal solution) method, reflects the degree of container demand in destination cities. Then, we describe five scenarios against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Chang et al (2013) examined GHG emissions from port shipping activities in Korea's Port of Incheon and found significant differences when comparing the results of the bottom-up approach with the top-down approach. Additionally, several studies have discussed the best possible measures for climate mitigation in the maritime transportation sector (Li et al, 2019;MERSIN et al, 2019;Prasad and Raturi, 2019;Jiang et al, 2020;Joung et al, 2020;Zincir, 2020;Al-Enazi et al, 2021;Inal et al, 2021). However, no study has been found that explores and compares the overall GHG emission scenario from the maritime transportation sector by taking into account all types and sizes of maritime vesselsa research gap that is explored in this study.…”
Section: Review Of Methodologies and Emission Factorsmentioning
confidence: 99%
“…Chang et al (2013) examined GHG emissions from port shipping activities in Korea's Port of Incheon and found significant differences when comparing the results of the bottom-up approach with the top-down approach. Additionally, several studies have discussed the best possible measures for climate mitigation in the maritime transportation sector (Li et al, 2019;MERSIN et al, 2019;Prasad and Raturi, 2019;Jiang et al, 2020;Joung et al, 2020;Zincir, 2020;Al-Enazi et al, 2021;Inal et al, 2021). However, no study has been found that explores and compares the overall GHG emission scenario from the maritime transportation sector by taking into account all types and sizes of maritime vesselsa research gap that is explored in this study.…”
Section: Review Of Methodologies and Emission Factorsmentioning
confidence: 99%
“…To measure the development level of the tea industry-tourism-ecological environment system, it was necessary to determine the weight of each indicator. Compared with the AHP method, the entropy weight method is more objective when determining weights based on the information contained in each indicator [33,59]. In this study, the data of Fujian Province were selected to calculate the weights using the entropy weight method.…”
Section: Entropy Weight Methodsmentioning
confidence: 99%
“…Tran and Haasis (2015) emphasize the necessity of ocean carrier holistic approaches in port selection that consider both maritime and hinterland operations to align shipping practices with global sustainability goals. Complementing this, Li, Kuang, and Hu (2019) elucidate the significant impact of port selection on environmentally friendly shipping routes, using the entropy weight TOPSIS method to highlight how quantitative models integrated into China's container development strategy can effectively reduce CO2 emissions and enhance multimodal transport systems. Additionally, Wang and Yeo (2019) investigate the selection of transshipment hub ports through a case study of Shanghai and Ningbo, emphasizing that cost, hub port space allocation, and connectivity are essential for balancing economic efficiency and environmental sustainability in port operations.…”
Section: Mt'24 10th International Conference On Maritime Transportmentioning
confidence: 99%